Anomalous reduction in the long-time flux creep relaxation in superconducting Ca10(Pt4As8)((Fe1-xPt x )2As2)5 (x ≈ 0.05) single crystals - Haberkorn, Nestor Fabian; Huang, Silu; Jin, R. (IOP Publishing, 2018)
Fil: Haberkorn, Nestor Fabian. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte; Argentina. Comisión Nacional de Energía Atómica; Argentina. Comisión Nacional de Energía Atómica. Gerencia del Área de Energía Nuclear. Instituto Balseiro; Argentina